2023
DOI: 10.3390/fire6030099
|View full text |Cite
|
Sign up to set email alerts
|

Intense Wildfires in Russia over a 22-Year Period According to Satellite Data

Abstract: The spatiotemporal distributions of wildfire areas and FRP values for the territory of Russia and its large regions (the European part of Russia, as well as the Ural, Siberian, and Far Eastern Federal Districts) during 2001–2022 were analyzed using satellite data. For the territory of Russia, there was a decreasing trend in annual burned areas and a small increase in average hotspot FRP. At the same time, the largest annual burned areas in the territory of Russia were recorded in 2008 (295.2 thous. km2), 2002 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Several studies have investigated the dynamics of forest fire behaviour and burnt areas in the different regions of the Russian Federation [13,[52][53][54][55][56]. These studies have revealed differences in the sensitivity of forest fire regimes to climate change and fire return interval (FRI) variability across the territory of the Russian Federation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the dynamics of forest fire behaviour and burnt areas in the different regions of the Russian Federation [13,[52][53][54][55][56]. These studies have revealed differences in the sensitivity of forest fire regimes to climate change and fire return interval (FRI) variability across the territory of the Russian Federation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, longer living gaseous emissions from Siberian fires fill almost completely the extratropical latitudes of the Northern Hemisphere [6,7]. The 2021 fires in Yakutia (Sakha) and the Krasnoyarsk region of Russia attracted particular attention [8,9].…”
Section: Introductionmentioning
confidence: 99%